Ruling Myanmar : from cyclone nargis to national elections (Singapore : Institute of Southeast Asian Studies, 2010)
November 2010 sees the first elections in Myanmar/Burma since 1990, to be held as the culmination of the military regimes'Road Map for Democracy'. The conditions under which the elections are being held are far from favourable, although the laws and procedures under which they will be conducted have been in place for seven months and quite widely publicized. Political controls remain repressive, freedom of expression and assembly does not exist, and international access is restricted by government controls as well as sanctions.
Cover, Title,Ruling Myanmar : from cyclone nargis to national elections--Preface, Introduction, TOC,Table of Contents--References, Appendix, Index,List of Abbreviations--References, Appendix, Index,Index.
Keywords: Cyclone Nargis, 2008 -- Congresses; Humanitarian assistance -- Burma -- International cooperation -- Congresses